Aplicação de redes neurais artificiais no setor de transportes no Brasil - Corrêa, Fernanda (Universidade Federal de São Carlos, 2008)
The development of Artificial Neural Networks in the Brazilian´s Sector of Transports comes carrying through great done in what it refers to the promotion of the use of the technique in the solution of problems found in this area. Artificial Neural Networks are computational techniques with capacity to simulate the cerebral activity human being, making future forecasts from the analysis of data. This technique, throughout the years comes greatly stimulating the research in planning of transports in such a way in the exterior how much in Brazil. As objective, this work brings an exploratory research, trying to lift the state of the art of the use and application of the technique Artificial Neural Networks in the Section of Transports in Brazil, drawing a comparison of what has been accomplished at the developed countries and in Brazil. In Brazil, the ANNs had started to be developed in the Sector of Transports for return of the years of 1990, today, the research in this area is generating important works very for the planning of transports, however, the technique of Artificial Neural Networks still has much to be improved better to be used as administrative tools in the country.
Keywords: Planejamento dos transportes; Redes neurais (Computação); Brasil - ciência e tecnologia - desenvolvimento; Redes neurais artificiais; Desenvolvimento brasileiro; Artificial neural networks; Sector of transports; Brazilian development; ENGENHARIAS